Effects of Preheating Temperature on Deformed AA6061 Aluminium Properties of Hot Equal Channel Angular Pressing (ECAP) by Using Deform-3D Software - Sami. Al-Alimi, Sami. Al-Alimi; Mohd. Amri. Lajis, Mohd. Amri. Lajis; Shamsudin, Shazarel; Yusuf, Nur Kamilah; Yahya Altharan, Yahya Altharan; Djamal Hissein Didane, Djamal Hissein Didane; Saif, Yazid; Sadeq, Safwan; M. Sabbar, Huda; S. Msebawi, Muntadher i (2022)
In this paper, the deformation characteristics of engineering AA6061 aluminium in the Equal Channel Angular Pressing (ECAP) are performed using the deformed 3D software. This study is designed to use 0.01 friction, 80,000 number of elements, and 450C, 500C, 550C preheating temperature. The study investigates the effects of die factors such as ECAP outer or inner ingles, die displacement, strength coefficient applied punch force, strain homogeneity, and strain distribution. Moreover, the hot ECAP die factors have played an essential role in the magnitude of material effective strain. On the one hand, decreasing die angles leads to imposing more strain with higher punch force on the workpiece, which results in more homogeneity of the processed materials. On the other hand, stress distribution mainly occurs at the die corner of the die, raising the temperature gradient. In comparison mechanical and physical properties which show an important agreement to support the importance of temperature processing gradient investigations. The study confirms that preheating temperature and friction values play a significant role in hot ECAP materials forming and die safety.